DIAGNOSIS HARA MAKRO PADA TANAMAN JATI (Tectona grandis L. f.) DENGAN METODE DRIS, M-DRIS DAN CND - , SURYANAJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Teak Plus Perhutani Clone needs a diagnosis method for its nutrient management. DRIS (Diagnosis and Reccomendation Integrated System), M-DRIS (Modified-Diagnosis Recommendation Integrated System) and CND (Compositional Nutrient Diagnosis) are used to diagnosis nutrient balance by considering the interaction between nutrient in plant tissues. The objectives of this research to determine the best diagnosis method, fertilizing effect on Jati Plus Perhutani nutrient balance and the order of macronutrient requirement.Fertilizing study of Urea, TSP and KCl and their dosage were conducted in KPH Randublatung. Low teak productivity sample taken from KPH Cepu and high productivity from KPH Ngawi on 28 month old plantation. Measurement and foliar sampling were conducted in 2013. Parameters measured were height, diameter, volume, and total of foliar nutrient of nitrogen (N), phosporus (P), potassium (K), calsium (Ca) and magnesium (Mg).Correlation between plant volume and M-DRIS index (0,60) better than DRIS (-0,56) or CND (-0,41), because M-DRIS method have calculated two pair of nutrient interaction and accommodate another nutrients that are not include it. Fertilizing of Urea 50g + TSP 50g + KCl 25 g produce nutrient balance base on M-DRIS index (1,81) better than control (3,83) and changes the order of nutrient requirement from Mg>P>K>N>Ca on control into P>K>N>Mg>Ca. Land status are defficiency P and excess Ca because fixation P by Ca, so it needs better P nutrient management. Keywords: diagnosis, nutrient balance, plant tissue, plus clone, teak